Hemodynamic trajectories and outcomes in patients with pulmonary arterial hypertension. (1st December 2020) - Amsallem, Myriam; Bagherzadeh, Shadi P.; Boulate, David; Sweatt, Andrew J.; Kudelko, Kristina T.; Sung, Yon K.; Feinstein, Jeffrey A.; Fadel, Elie; Mercier, Olaf; Denault, Andre; Haddad, Francois; Zamanian, Roham
Abstract : The relative pulmonary to systemic pressure ratio (mean pulmonary arterial pressure/mean arterial pressure) has been proven to be valuable in cardiac surgery. Little is known on the prognostic value of baseline and trajectory of mean pulmonary arterial pressure/mean arterial pressure in pulmonary arterial hypertension. Patients with confirmed idiopathic, familial, drug and toxins, or connective tissue disease‐related pulmonary arterial hypertension and at least one complete right heart catheterization were included and prospectively followed‐up for 5.9 ± 4.03 years. Correlates of the primary end point (i.e. death or lung transplant need) during follow‐up were determined using Cox regression modeling. Results showed that among the 308 patients included, 187 had at least one follow‐up catheterization (median time between catheterizations: 2.16 (1.16–3.19) years). In the total cohort (mean age 47.3 ± 14.9 years, 82.8% of female and 58.1% in New York Heart Association class 3 or 4), mean pulmonary arterial pressure/mean arterial pressure (1.38 (1.07–1.77)) was associated with outcome ( p = 0.01). Mean pulmonary arterial pressure/mean arterial pressure was incremental to a basic model (including right atrial pressure, systolic blood pressure, New York Heart Association class 3 or 4, and connective tissue disease) for outcome prediction, while mean pulmonary arterial pressure was not. In the 187 patients with a follow‐up catheterization, both delta mean pulmonary arterial pressure and delta mean pulmonary arterial pressure/mean arterial pressure were associated with outcome (1.32 (1.11–1.58) and 1.31 (1.1–1.57) respectively, p < 0.01). Mean pulmonary arterial pressure and mean pulmonary arterial pressure/mean arterial pressure were both incremental to the basic model, while worsening in mean pulmonary arterial pressure or mean pulmonary arterial pressure/mean arterial pressure did not reach significance. In conclusion, mean pulmonary arterial pressure/mean arterial pressure at baseline prognosticates long‐term outcome with a significant, albeit modest, incremental value to basic variables.